2020
DOI: 10.3390/su12103983
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Sustainability in Farm Diversification Initiatives in Northern Spain

Abstract: The value-added diversification strategy provides an option for guaranteeing the sustainability of small farms. This study examines how factors related to managerial strategy and socio-environmental sustainability influence the efficiency of diversification initiatives. For this purpose, we use a novel and unique database of value-added ventures implemented by 49 dairy farms located in northern Spain. We construct a production frontier using a Data Envelopment Analysis (DEA) model to estimate technical efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…UAA/AWU presents a negative sign; this was an expected result since higher labour productivity raises efficiency. The positive sign of FWU/AWU indicates a reduction of the efficiency as family work units increase; this is in line with literature findings [19], which emphasizes how an increase in the incidence of family work is linked to worse performances in terms of efficiency. IrrUAA/UAA is significant, but only at 10% level; the possibility of irrigating increases land profitability [11], and, as a consequence, farm efficiency.…”
Section: Panel Tobit Regression Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…UAA/AWU presents a negative sign; this was an expected result since higher labour productivity raises efficiency. The positive sign of FWU/AWU indicates a reduction of the efficiency as family work units increase; this is in line with literature findings [19], which emphasizes how an increase in the incidence of family work is linked to worse performances in terms of efficiency. IrrUAA/UAA is significant, but only at 10% level; the possibility of irrigating increases land profitability [11], and, as a consequence, farm efficiency.…”
Section: Panel Tobit Regression Resultssupporting
confidence: 89%
“…In other words, in addition to its risk-reducing benefits, diversification offers the opportunity to exploit the complementary potential of the farm and a more efficient distribution of the family workforce, at the same time, minimizing the economic and entrepreneurial risk [18]. Moreover, the percentage of family work is often negatively associated with efficiency [19]; different results were obtained by Sabasi et al [20] that found a negative association between the (increase in) off-farm work by the farm household and the (decrease in) the efficiency of U.S. dairies.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…This class uses conventional marketing channels like direct sales and wholesaler markets (Barrowclough et al, 2019;Micheels and Boecker, 2017;Tudisca et al, 2014). Even neglecting more unconventional approaches, farm diversification of traditionalists is essential to the economic sustainability of smaller farms and the enhancement of cultural and traditional features of rural zones (Garc ıa-Cornejo et al, 2020).…”
Section: Farm Diversificationmentioning
confidence: 99%
“…The milk quota system was introduced in the EU in 1984 (2004 for the New Member states, when they entered the EU) and continued until its abolition in 2015. The largest quota holders in the 28 EU countries in 2014/2015 were Germany (19.6% of total), France (17.1%), United Kingdom (10.3%), The Netherlands (7.8%), Italy (7.3%) and Poland (6.5%), and relatively small quota were owned by Lithuania (1.2%) and Slovenia (0.4%) (EU total quota was 154.6 million tons; European Technical and productive potential and structural outlook on the dairy sector have been widely discussed and described [10][11][12][13][14]. Also farmers' attitudes or opinions toward policies have been analysed in Western Europe [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In Australia and New-Zealand interactive stakeholder studies were being performed presenting various scenarios for strategic development of the dairy communities [27]. Technical and productive potential and structural outlook on the dairy sector have been widely discussed and described [10][11][12][13][14]. Also farmers' attitudes or opinions toward policies have been analysed in Western Europe [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%